Phytoseiid mites (Acari: Phytoseiidae) from Patagonia and Tierra del Fuego - Ferragut, Francisco; Navia, Denise (Zootaxa, 2015)
Predatory phytoseiid mites have been intensively studied and surveyed in the last decades because of their economic importance as biocontrol agents of agricultural pests. However, many regions of the world remain unexplored and the diversity of the family worldwide is still fragmentary. Up to date no phytoseiid species have been collected in the southernmost part of the Earth down to latitude 45º S. In this study Phytoseiidae were sampled from native vegetation in southern Argentina and Chile in the regions of Patagonia and Tierra del Fuego Island. Thirteen species were collected, five of which were previously described and eight, Chileseius australis n. sp., Neoseiulus mapuche n. sp., Typhlodromips valdivianus n. sp., T. fissuratus n. sp., Amblyseius grandiporus n. sp., A. caliginosus n. sp., Typhlodromus (Anthoseius) anomalos n. sp. and Metaseiulus parabrevicollis n. sp. are proposed as new to science and are described and diagnosed.